Between Realism of Observation and a Vision: The Creative Process and the Value of Its Result Using the Example of The First Part of Zygmunt Krasiński’s "The Un-Divine Comedy" - Kuczera-Chachulska, Bernadetta (Colloquia Litteraria, 2018)
A case study of Zygumnt Krasiński’s The Un-Divine Comedy. The article touches upon the characteristics of Zygmunt Krasiński’s creative process. The author analyses this issue in reference to the wellestablished in the history of literature argument of predominantly intellectual, historiosophical and visionary background to Krasiński’s writing. Using the example of the first part of The Un-Divine Comedy, she brings forward an argument on the weight and relevance of realistic observation of reality in the writings of this romantic author.